Implementation of Indonesian Language Assessment Class VIII Based on Pancasila Student Profile and Digital Literacy Oriented - Sri Isnani Setiyaningsih; Ahmad Muthohar; Anis Malik Thoha (Jurnal Sastra Indonesia, 2026)
This study aims to describe the implementation of Indonesian language assessment for eighth-grade students based on the Pancasila Student Profile and oriented toward digital literacy. This study uses a mixed methods approach with an explanatory sequential design, focusing on the planning, implementation, and [evaluation/reporting] evaluation processes of assessment that integrate the dimensions of the Pancasila Student Profile along with the use of digital technology. The research subjects include teachers and eighth-grade students at the junior secondary school level. Data were collected through questionnaire, observation, interviews, and documentation. The findings indicate that the assessment implementation has incorporated the values of the Pancasila Student Profile, such as critical thinking, creativity, and independence, and has begun to utilize digital media in the assessment process, including online learning platforms and digital evaluation tools. However, several challenges remain, including teachers’ readiness, limited infrastructure, and varying levels of students’ digital literacy. Therefore, strengthening teachers’ competencies and improving infrastructure support are essential to optimize the implementation of assessment based on the Pancasila Student Profile and digital literacy.